Improkunstens værdi: Litterære jazzdiskurser i Norden - Strauß, Frithjof (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2010)
The Value of Impro Art. Literary Jazz Discourses in Scandinavia In later times, much of the study of jazz and jazz culture has taken place within the field of Cultural studies. While this has led to valuable insights into the manifestations of collective divisions such as social class, age, gender, and ethnicity in historical texts and images associated with jazz, the aesthetic dimension of the music itself has been more or less neglected. In opposition to this bias, the present article concentrates on the reception of the artistic morphogenesis in jazz music. Jazz, which can be defined ideally as improvised meta-music, came to Europe during the prime of the modernism of classical art music. This was a time also of avantgarde movements, and there is reason to compare jazz to this counter-development. Like other avant-garde arts, jazz dissolves the semantics of the work/the composition (by virtue of its improvisation) as well as the contemplative mode of reception associated with classical art music. At the same time, jazz is entertaining music with an appeal to the mainstream and mass media and with a strong emotional effect on the listener. In the resulting field of tension, jazz soon became a subject for literature in the Nordic democracies. Taking an inter-Nordic perspective, the article briefly examines when and how poetry’s representatives took jazz seriously as an art form. It is pointed out that this estimation took place only when poetic modernism had been incontestably established as part of the national literatures.